DIGITAL UNCERTAINTY IN ISLAMIC BUSINESS LAW: A SYSTEMATIC LITERATURE REVIEW ON GHARAR AND MAISIR IN CONTEMPORARY E-COMMERCE TRANSACTIONS - Lutfi Maulana; Ikmal Mumtahaen; Muhammad Romli; Ahmad Khaliq (JURNAL HAKAM, 2026)
The rapid expansion of e-commerce and digital financial technologies has transformed contemporary business practices, generating new forms of contractual uncertainty that challenge established principles of Islamic business law. Central to this challenge are the classical prohibitions of Gharar (excessive uncertainty) and Maisir (speculative gain), which function as core ethical and legal benchmarks for evaluating the permissibility of commercial transactions under Shariah. Despite a growing body of scholarship addressing these issues, existing studies remain fragmented across normative, empirical, and theoretical approaches, with limited systematic synthesis. This article addresses this gap by conducting a systematic literature review (SLR) of Scopus-indexed journal articles published between 2015 and 2025 that examine Gharar and Maisir in contemporary e-commerce and digital financial transactions.Applying a PRISMA-guided methodology, the review analyzes 36 unique studies and synthesizes findings across four analytical dimensions: study characteristics and quality, theoretical foundations, thematic patterns of digital transactions, and methodological trends with associated research gaps. The findings reveal strong scholarly convergence on the centrality of contractual transparency, informed consent, and risk mitigation as prerequisites for Shariah compliance in digital transactions. At the same time, significant divergence persists regarding the scope of acceptable uncertainty, particularly in relation to emerging technologies such as cryptocurrencies and gamified e-commerce models. The review further demonstrates that Gharar functions as the dominant conceptual gateway for regulating digital commerce, while Maisir operates as a critical boundary marker in cases of extreme speculation.This study contributes to Islamic business law scholarship by offering an integrated conceptual and methodological map of existing research, clarifying areas of consensus and contestation, and identifying priority directions for future inquiry. The findings underscore the need for adaptive regulatory frameworks, empirically informed legal analysis, and purposive interpretation grounded in maqāṣid al-sharīʿah to ensure that Islamic legal principles remain ethically robust and practically relevant in the digital economy